HUBUNGAN KEMAMPUAN NUMERIK DAN PERSEPSI SISWA TERHADAP PELAJARAN MATEMATIKA DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMPN 2 JOGONALAN KLATEN TAHUN AJARAN 2012/2013 - Tesi Kumala Sari; Esti Harini (Universitas Sarjanawiyata Tamansiswa, 2015)
The purpose of this research is to find out the correlation between numerical ability and students perception on mathematics with the results of mathematics learning. This research method applied descriptive of correlation. The population in this research is grade VIII SMPN 2 Jogonalan totaling 171 students, with a sample of 86 students taken by cluster random sampling. Analytical techniques multiple regression analysis with requirment of normality and linierity. Based on the results of the research, R = 0,491, meaning that there was a positive correlation between numerical ability and students perception on mathematics with the results of mathematics learning. 0,533, meaning that there was a positive correlation between numerical ability with the results of mathematics learning. 0,307, meaning that there was a positive correlation between students perception on mathematics with the results of mathematics learning.